2020
DOI: 10.1039/c9nr10779g
|View full text |Cite
|
Sign up to set email alerts
|

Multi-triggered and enzyme-mimicking graphene oxide/polyvinyl alcohol/G-quartet supramolecular hydrogels

Abstract: 3D-nanostructured supramolecular hydrogels were fabricated via self-assembly of GO nanosheets, PVA chains, and G-quartet/hemin motifs, showing multi-triggered switchable behaviors as well as excellent peroxidase-like activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…This article is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported Licence. View Article Online DOI: 10.1039/D2MA00034Bby color change as shown in Fig.8f, and this can be explored for the designing of bioelectronic material with good chemical functionality 153.…”
mentioning
confidence: 99%
“…This article is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported Licence. View Article Online DOI: 10.1039/D2MA00034Bby color change as shown in Fig.8f, and this can be explored for the designing of bioelectronic material with good chemical functionality 153.…”
mentioning
confidence: 99%
“…The findings revealed that the NIDN hydrogel system might be easily changed into a new kind of magnetic reactive hydrogel that supports the cell growth of bone marrow mesenchymal stem cells and has the ability to repair calvarial defects. Zhang et al used self-fabrication of graphene oxide (GO) nanosheets, poly (vinyl alcohol) (PVA) chains, and G-quartet/hemin (G4/H) motifs to create a three-dimensional (3D) supramolecular hydrogel exhibiting stimuli-responsive characteristics in aqueous environments [ 286 ]. The GO/PVA/G4/H hydrogel had a honeycomb-like 3D GO lattice architecture and outstanding mechanical characteristics as it was manufactured.…”
Section: Applications Of 4d Printed Hydrogelsmentioning
confidence: 99%
“…Consequently, these are not quite successful for field applications, which limits their usage. To overcome these disadvantages, many alternate approaches have been proposed wherein the 2D materials like molybdenum disulfide, 138 cobalt oxyhydroxide nanosheets, 139 graphene, 140 etc. have been utilized for hydrogen peroxide detection.…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%